Mandatory Wills for Adultery Children, Analysis of the Compilation of Islamic Law from the Perspective of Maqasid Syariah Al-Syatibi - Arifin, Zainal; Mahmudi, Zaenul (NAJAHA, 2022)
The development of Islamic law in Indonesia from time to time shows quite rapid development, both from the legal institutionalization process and contemporary Islamic studies, one of which is the obligatory will as stated in the Compilation of Islamic Law (KHI) Article 209 Paragraphs 1 and 2. The obligatory will What is meant in this KHI is the taking of assets from adoptive parents to adopted children or from adopted children to adoptive parents through a mandatory court decision, whether the person who died said or wrote a will while alive or not. This research aims to explain the mandatory will in the KHI in its application to children of adultery as protection against them. This article uses a library research approach and a philosophical qualitative-juridical method, then analyzed using maqasid syari'ah al-Syatibi, seen from the perspective of dalil, illah, and the benefits of justice which are in accordance with the objectives of shari'ah. From the discussions carried out, the result was found, namely that a mandatory will is a mandatory message and must be implemented. A child resulting from adultery who is born in a pure state without sin and is not worthy of receiving the prayers of his parents has the right to be protected from weakness and misery after the death of his mother and father, so with a mandatory will which is confirmed by the testament of Surah al-Nisa verse 9 which commands to be devoted to Allah Swt.